Mice with Deficiency of G Protein γ(3) Are Lean and Have Seizures - Schwindinger, William F. (Mol Cell Biol, 2004)
Emerging evidence suggests that the γ subunit composition of an individual G protein contributes to the specificity of the hundreds of known receptor signaling pathways. Among the twelve γ subtypes, γ(3) is abundantly and widely expressed in the brain. To identify specific functions and associations for γ(3), a gene-targeting approach was used to produce mice lacking the Gng3 gene (Gng3(−/−)). Confirming the efficacy and specificity of gene targeting, Gng3(−/−) mice show no detectable expression of the Gng3 gene, but expression of the divergently transcribed Bscl2 gene is not affected. Suggesting unique roles for γ(3) in the brain, Gng3(−/−) mice display increased susceptibility to seizures, reduced body weights, and decreased adiposity compared to their wild-type littermates. Predicting possible associations for γ(3), these phenotypic changes are associated with significant reductions in β(2) and α(i3) subunit levels in certain regions of the brain. The finding that the Gng3(−/−) mice and the previously reported Gng7(−/−) mice display distinct phenotypes and different αβγ subunit associations supports the notion that even closely related γ subtypes, such as γ(3) and γ(7), perform unique functions in the context of the organism.